O consentimento na Lei geral de proteção de dados e o problema da assimentria informacional : soluções a partir da cláusula geral da boa-fé objetiva - Toniazzo, Daniela Wendt (2022)
The Brazilian General Data Protection Law (LGPD) represents a very important legal framework for the protection and guarantee of the human person, since it facilitates the control of processed data, imposes duties and responsibilities on the agents involved and provides security for the information to circulate. Informative self-determination was recognized as one of the foundations of the LGPD and grants the individual the right to decide on the use of their personal data; while consent, the main legal basis for the processing of personal data, is a fundamental instrument for the exercise of this right. In turn, the insertion of the general clause of objective good faith, in the caput of article 6 of the LGPD, imposes an ethical and loyal standard of conduct for all characters involved in the processing of personal data, especially those who have mastery of technologies that collect this information and that are responsible for ensuring the privacy of users. In this context, the legal conduct resulting from the objective good faith of the data controllers will be identified, in order to find alternatives to mitigate the information asymmetry present in these relationships; as well as the connection between objective good faith and privacy by design as a necessary structure to protect the confidence of holders about the security of their information at the time of consent.